A thousand Texas longhorns - Boggs, Johnny D. (Pinnacle Books, Kensington Publishing Corp., 2023)
"The Civil War is over. The future of the American West is up for grabs. Any man crazy enough to lead a herd of Texas longhorns to the north stands to make a fortune--and make history. That man would be Nelson Story. A bold entrepreneur and miner, he knows a golden opportunity when he sees one. But it won't be easy. Cowboys and bandits got guns, farmers got sick livestock, and the Army's got their own reasons to stop the drive. Even worse, Story's top hand is an ornery Confederate veteran who used to be his enemy. But all that is nothing compared to the punishing weather, the deadly stampedes--and the bloodthirsty wrath of the Sioux...This is the incredible saga of a man named Story. A true legend of the Old West. And the ever-beating heart of the American Dream."--Back cover.